THE MAIN CAUSES OF UNSATISFACTORY OUTCOMES OF TREATMENT FOR FOOT INJURIES - V. O. Kalensky; P. A. Ivanov (Неотложная медицинская помощь)
Background. The foot is a special anatomical structure in its complexity. A large number of articular and ligamentous structures provide effective amortization and adaptation to surface features when walking. At the same time, if it is damaged, restoration of its anatomic structure is significantly difficult for a surgeon and may cause a number of complications and consequences. These issues are significant in patients with multisystem and multiple trauma.Aim of study. To identify the most common causes of unsatisfactory outcomes of treatment for foot injuries in patients with isolated, multiple and multisystem trauma.Material and methods. Treatment of 216 patients was analyzed. We revealed 129 fractures of the calcaneus, 25 fractures of metatarsal bones and/or toes of the foot, 21 fractures of the talus, 18 Lisfranc lesions, 13 fractures of midfoot bones, and 10 multiple trauma of the foot. The multisystem trauma occurred in 38.4% of cases, isolated trauma of the foot was revealed in 36.7% and multiple injuries were observed in 24.9%. When evaluating the results, early and late complications were taken into account, and the functional outcome was determined by the Foot Function Index (FFI) after 6, 12 and 24 months.Results. Among patients with closed fractures of the calcaneus, the problems of healing of the postoperative wound appeared in 3.5% of cases in operative treatment. The frequency of secondary displacements was 5.8%. By 24 months in patients after surgical and conservative treatment, similar functional outcomes were observed. Among patients with open fractures, skin necrosis occurred in 7 out of 25 cases and wound infection was observed in 15 cases. When fixing with wires, secondary displacement was observed in 4 cases out of 18. The average FFI score by 24 months was 59.5. In patients with forefoot fractures, wound healing complications occurred in 2 cases. The average score on the FFI scale was 93.7±8.1. In patients with fractures of the talus, wound complications were not noted, avascular necrosis (AVN) developed in 9 patients, osteoarthrosis (OA) developed in 15 cases. The average FFI after 2 years was 93.2±5.5 in patients without AVN and OA, and 63.6±23.1 in patients with AVN and/or OA. Among patients with midfoot trauma, infectious complications and secondary displacement were not observed. Osteoarthrosis occurred in 13 patients, including 8 patients with lesions of the Lisfranc joint. The difference in functional outcomes between patients with developed osteoarthrosis and without it differed in mean values, but was not statistically significant.Conclusion. The causes of unsatisfactory outcomes of treatment for foot trauma are wound complications against the background of open fractures of the calcaneus, avascular necrosis of the talus and posttraumatic arthrosis of the foot joints. It is advisable to continue research to find the best algorithm for treatment in these cases.